Unmanned systems in large-scale combat operations: a scoping review of their impact and integration in prolonged casualty care - Chloé Waters; Attila J. Hertelendy; Fadi Issa; Williams Lopez Vidal; Amalia Voskanyan; Gregory Ciottone (Journal of Emergency and Disaster Medicine, 2026)
Abstract Background Large-scale combat operations (LSCO) have disrupted prior battlefield healthcare models reliant on rapid evacuation and the “Golden Hour.” In contemporary conflicts, including Ukraine, Gaza, Sudan, and Iran, care is often delivered in highly contested environments with degraded infrastructure and persistent surveillance, where evacuation is frequently delayed or denied. This has necessitated a shift toward prolonged casualty care (PCC). Although unmanned systems (UxS) demonstrate utility in civilian and humanitarian medical delivery, their integration into active-conflict trauma care and their impact on clinical outcomes remain poorly defined. Methods A scoping review was conducted using the Arksey and O’Malley framework. Four databases (OVID MEDLINE, Embase, Web of Science, and CINAHL) were searched for studies on unmanned systems in conflict environments. Analysis focused on UxS context, injury patterns, and applications in resupply, evacuation, and PCC. Results Seven studies met the inclusion criteria. UxS were not evaluated as clinical interventions but were consistently described in offensive roles contributing to injury patterns and medical operations disruption. No included studies demonstrated UxS use for medical evacuation, resupply, or clinical care delivery. Conclusion UxS currently shape both injury patterns and the forward medical environment but remain poorly evaluated in the literature for integration into trauma care delivery and prolonged casualty care (PCC). A critical evidence gap persists regarding their role in medical evacuation, resupply, and clinical support. Future research should prioritize UxS integration and outcome-based evaluation of UxS use within PCC frameworks.